The Gulf Stream moved northward at the end of the Little Ice Age - Edward C. G. Forman; James U. L. Baldini; Robert A. Jamieson; Franziska A. Lechleitner; Izabela W. Walczak; Dan C. Nita; Struan R. Smith; David A. Richards; Lisa M. Baldini; Cameron McIntyre; Wolfgang Müller; Andrew J. Peters (Communications Earth & Environment)
Abstract The Gulf Stream forms part of the upper-ocean limb of the Atlantic Meridional Overturning Circulation, playing an essential role in redistributing heat northward and greatly influencing regional climates in the North Atlantic. Understanding Gulf Stream path and strength variability on pre-instrumental timescales is vital to contextualise its proposed present-day weakening and to better appreciate its sensitivity to external forcing. Here we present a 564 year-long monthly resolved terrestrial palaeo-oceanographic temperature record derived from a Bermudan stalagmite, spanning 1449 to 2013 in the Common Era. Our reconstruction suggests that the Gulf Stream migrated northward as the Little Ice Age abated, after a combination of reduced Gulf Stream transport, enhanced Labrador Current and Deep Western Boundary Current transport, and an extended negative North Atlantic Oscillation phase had likely forced its path southward.